Future directions for scholarship on data governance, digital innovation, and grand challenges. Issue 1 (March 2023) - Davidson, Elizabeth; Wessel, Lauri; Winter, Jenifer Sunrise; Winter, Susan
Abstract: This introduction to the special issue on Data Governance, Digital Innovation, and Grand Challenges highlights the importance of data governance when seeking to address grand challenges through the innovative use of digital technologies. The benefits, risks, and consequences of data, ubiquitous in today's data-rich world, can be harnessed for innovation and societal good. However, there are no guarantees that (only) desirable outcomes will develop. The creation and exploitation of vast data stockpiles raise substantial concerns about privacy, data security, equity, and the potential for harm from data misuse. Meaningful approaches to data governance within and across organizations are critically important to facilitate digital innovation and to balance social, economic and technical benefits and risks for individuals, organizations, and societies. In this introductory paper, we reflect on foundations established to date in information systems (IS) research and highlight possible future directions for scholarship on data governance across multiple levels to enhance digital innovations for transformation and societal good. Highlights: This article discusses research in the IS field on data governance in light of emerging governance issues and challenges. The article outlines five themes for future data governance research aimed at addressing social issues through data and innovation. The article gives an overview of the contributions to this special issue on data governance, digital innovation and grand challenges.